NGUI for Unity: master NGUI components swiftly, and employ them to create a thrilling, action-packed 2D sci-fi game - Bernardoff, Charles (PACKT Publishing, 2014)
An easy-to-follow, step-by-step tutorial focusing on practical situations and manipulations, guiding you to create a concrete Graphical User Interface and a simple 2D game. If you are a Unity 3D developer looking forward to learn NGUI for Unity, then this book is for you. Prior knowlege of C♯ scripting is expected. Additional knowledge of Unity 3D Editor, GameObject and creating/adding scripts to GameObject would be beneficial; however, no prior knowledge of NGUI is required.